Ectopic Fatty Acid–Binding Protein 4 Expression in the Vascular Endothelium is Involved in Neointima Formation After Vascular Injury. Issue 9 (13th September 2017) - Fuseya, Takahiro; Furuhashi, Masato; Matsumoto, Megumi; Watanabe, Yuki; Hoshina, Kyoko; Mita, Tomohiro; Ishimura, Shutaro; Tanaka, Marenao; Miura, Tetsuji
Abstract : Background: Fatty acid‐binding protein 4 (FABP4) is expressed in adipocytes, macrophages, and endothelial cells of capillaries but not arteries. FABP4 is secreted from adipocytes in association with lipolysis, and an elevated circulating FABP4 level is associated with obesity, insulin resistance, and atherosclerosis. However, little is known about the link between FABP4 and endovascular injury. We investigated the involvement of ectopic FABP4 expression in endothelial cells in neointima hyperplasia after vascular injury. Methods and Results: Femoral arteries of 8‐week‐old male mice were subjected to wire‐induced vascular injury. After 4 weeks, immunofluorescence staining showed that FABP4 was ectopically expressed in endothelial cells of the hyperplastic neointima. Neointima formation determined by intima area and intima to media ratio was significantly decreased in FABP4‐defficient mice compared with that in wild‐type mice. Adenovirus‐mediated overexpression of FABP4 in human coronary artery endothelial cells (HCAECs) in vitro increased inflammatory cytokines and decreased phosphorylation of nitric oxide synthase 3. Furthermore, FABP4 was secreted from HCAECs. Treatment of human coronary smooth muscle cells or HCAECs with the conditioned medium of Fabp4 ‐overexpressed HCAECs or recombinant FABP4 significantly increased gene expression of inflammatory cytokines and proliferation‐ and adhesion‐related molecules in cells, promoted cell proliferation and migration of human coronary smooth muscle cells, and decreased phosphorylation of nitric oxide synthase 3 in HCAECs, which were attenuated in the presence of an anti‐FABP4 antibody. Conclusions: Ectopic expression and secretion of FABP4 in vascular endothelial cells contribute to neointima formation after vascular injury. Suppression of ectopic FABP4 in the vascular endothelium would be a novel strategy against post‐angioplasty vascular restenosis.